EVALUATION OF IN VITRO CYTOTOXIC AND ANTICANCER ACTIVITY OF HEPATOPROTECTIVE POLYHERBAL FORMULATION IN CELL LINE MODEL - JAYACHANDRA KUNCHA; THIRUGNANASAMBANTHAM P; KUMARAN S; NARAYANAN N; SHARMILA DEVI V (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Introduction: The use of natural products as anticancer agents has a long history that began with folklore medicine and through the years has been incorporated into traditional and allopathic medicine. Several drugs currently used are derived from medicinal plants. Objective: The main objective of this study is to investigate the cytotoxic potential of hepatoprotective polyherbal formulation in normal and cancer cell lines. Methods: A 3-(4,5-dimethythiazol-2-yl)-2,5-diphenyltetrazolium bromide assay was utilized to screen the cytotoxic activity. Results: The results revealed that the formulation does not induce much mortality in normal liver and kidney cell lines, and LC50 value of liver cell lines was found 1716.355 μg/ml and kidney cell lines 2464.910 μg/ml. The in vitro anticancer activity was performed on liver, colon, and prostate cancer cell lines, and IC50 values are found 2.077, 3.850, and 11.989 μg/ml, respectively, which show excellent anticancer activity. Conclusion: Based on the results obtained, the hepatoprotective polyherbal formulation is safe for normal cells and cytotoxic for cancer cells. Further, identification and quantification of phytoconstituents responsible for the activity are in progress.